Mouse models of autoimmune diseases - autoimmune myocarditis - Müller, Anna-Maria; Fischer, Andrea; Katus, Hugo (Current pharmaceutical design, 2015)
Cardiovascular diseases are the leading cause of death in industrialized nations worldwide. Of all deaths - resulting from cardiovascular diseases, 2% are ca...
Gesehen am 20.07.2020